Business Plan As An Effort To Revitalization Of Bumdes In Air Latak Village, Seluma Barat District, Seluma Regency - Hidayat, Taofik; Soleh, Ahmad; Kresnawati, Kresnawati (Journal of Law, Social Science, and Management Review, 2025)
A sound business plan will help BUMDes develop, optimize local resources, and improve community well-being. With a well-thought-out plan, BUMDes can become a sustainable economic driver for the village. Therefore, revitalizing BUMDes in Air Latak Village, West Seluma District, Seluma Regency is crucial to maximize the village's economic potential, particularly in the tent and wedding stage business. The research findings indicate that Business Opportunities: The BUMDes in Air Latak Village, West Seluma District, Seluma Regency has significant potential in event equipment rentals, which can support the village’s economic empowerment. Vision and Mission: The BUMDes of Air Latak Village, West Seluma District, Seluma Regency aims to advance businesses, empower the community, preserve culture, and support the local economy. Business Goals: Appropriate performance indicators ensure that the objectives of the business—such as tents, chairs, and wedding stages—of BUMDes in Air Latak Village, West Seluma District, Seluma Regency are achieved and provide economic benefits for the village. Marketing Strategy: The strategy includes targeting the right market segments, local collaborations, and digital promotion to increase visibility and reach. Resources: Management training, digital marketing, and financial management are essential to improve efficiency and quality. Financial Plan: This includes funding sources, financial projections, and revitalization steps to ensure the business’s sustainability. Evaluation and Control: The evaluation of funding sources and financial projections ensures the sustainability and efficiency of the business.